E-litesense em rede de sensores sem fio com cluster em controlador externo - Mendonça, Mariano Florencio (2022)
The Internet of Things is a concept in technology that is constantly growing due to the amount of services that can be ofered, and the management of a wireless sensor network (WSN) represents one of the challenges for the community. Currently, not only computers are connected to the internet, but there is also a great heterogeneity of equipment. Working with this diversiőed sensor network with low processing and energy eiciency coeicient őts into several studies, including e-LiteSense, being a protocol that controls the communication of the sensor node according to the energy level. Organizing this network into clusters becomes another technique that aims to manage WSN communication, which generates greater processing for the sensor responsible for receiving information from the others and transmitting it to the base station. Thus, motivated by issues involving WSNs, this research aimed to develop an external controller responsible for controlling the virtual cluster network of wireless sensors, optimizing with the implementation of e-LiteSense, updating its internal parameters at runtime. The MQTT communication protocol (Message Queue Telemetry Transport) will be used to receive and send information from the wireless sensor network. This work őlls gaps involving the control of communication in WSNs and its management from an external environment.